البناء الفني للرسائل الإخوانية في العصر العباسي : The Artistic Construction of Informal Letters in Abbasid Prose - Dr Hafiz Haris Saleem (Al Manhal Research Journal, 2025)
Informal epistles constitute a significant literary genre that reflects the emotional, intellectual, and social dimensions of human interaction. During the Abbasid era, this genre reached remarkable maturity due to the cultural prosperity and literary refinement of the period. While Abbasid literature has been widely studied in poetry, philosophy, and science, informal epistolary prose has not received adequate scholarly attention despite its rich artistic and historical value.This study aims to examine the structural features of informal epistles (al-rasāʾil al-ikhwāniyyah) in the Abbasid period through a stylistic and rhetorical lens. It explores their linguistic patterns, expressive techniques, and rhetorical devices—such as simile, metaphor, and metonymy—while highlighting their social and emotional functions. The research adopts a descriptive-analytical approach, focusing on selected models of Abbasid epistolary writings to uncover their aesthetic and communicative dimensions.The study concludes that informal letters in the Abbasid era represent a mature literary form characterized by stylistic elegance, emotional depth, and rhetorical diversity, reflecting both the intellectual sophistication of their authors and the cultural vitality of their age.